Digital Authentic Assessment in Sentence Based Writing Course - Desi Wijayanti Ma’rufah (Proceeding International Conference on Religion, Science and Education, 2023)
The use of technology and digital literacy is increasing today, and implemented in the classroom. Authentic assessment provides students’ practices in real life activities. Higher education is more aligned with the practices of students’ future professions, which are becoming increasingly mediated by technology, when authentic assessment is used. This study aims to describe the use of authentic digital assessment in sentence-based writing course at English Education Study Program of UIN Saizu Purwokerto. A qualitative descriptive method was conducted through observation and documentation for collecting the data. The field notes and checklist were used as the instruments of the research. Instructional teaching materials and syllabus also used as the documents that were analyzed to support the data of observation. A lecturer was involved in this study as the subject of the study. The results show that the lecturer uses performance-based assessment using various mobile application; telegram, email, WhatsApp, Instagram and Canva. All the assessment activities fulfill the characteristics of authentic assessment. However, the lecturer did not implement all of the steps in assessing writing skill using authentic assessment that purposed by Brown. A holistic rubric is used to assess the students’ writing. This study is expected to provide pedagogical experiences in designing the authentic assessment using technology, especially in writing class.